Recombinant Bifidobacterium longum Carrying Endostatin Protein Alleviates Dextran Sodium Sulfate-Induced Colitis and Colon Cancer in Rats - Bi, Zhiqian; Cui, Enqing; Yao, Yingying; Chang, Xiaoyao; Wang, Xiaoyang; Zhang, Yuhui; Xu, Gen-Xing; Zhuang, Hongqin; Hua, Zi-Chun (Frontiers in Microbiology, 2022)
Bifidobacterium has been widely administrated orally as probiotics to prevent pathogen colonization and modulate the gut microbiome balance. Endostatin is an endogenous inhibitor of angiogenesis and has been shown to inhibit tumor growth, invasion, and metastasis. At present, the combination of endostatin and chemotherapeutic drugs has been regarded as a promising antitumor treatment strategy. In this study, we selected a safe strain of Bifidobacterium longum (B. longum) as a delivery system to transport endostatin to the gastrointestinal tract and explored their combined effect on inflammatory bowel disease and colitis-associated cancer. The results indicated that B. longum-Endo relieved DSS-induced body weight loss, diarrhea, colon shortening and epithelium damage. Long-term oral administration of B. longum-Endo significantly decreased tumor formation rate, tumor number, and tumor size. Moreover, the effect of B. longum-Endo on gut microbiota dysbiosis was also confirmed by 16S rRNA sequencing analysis. The levels of potentially beneficial bacteria, such as Lactobacillus, Bifidobacterium, Allobaculum, and Parabateroides, were increased in the B. longum-Endo group compared to the model and B. longum groups. Meanwhile, levels of potentially pathogenic bacteria including Desulfovibrio, Helicobacter and Enterorhabdus were decreased. Taken together, these results suggested that oral administration of recombinant B. longum-Endo strain may be a promising therapeutic strategy for inflammatory bowel disease and colitis-associated cancer.